I need to figure out how to derive it. I know you use partial fractions, but again with no numbers, the letters always change, part of it is my dyslexia.. thank you.
I need to figure out how to derive it. I know you use partial fractions, but again with no numbers, the letters always change, part of it is my dyslexia.. thank you.
$\displaystyle \frac{d+cx}{(x-a)(x-b)}=\frac{A}{x-a}+\frac{B}{x-b}\Rightarrow d+cx=A(x-b)+B(x-a)$ so A+B=c and -Ab-aB=d
So $\displaystyle A=\frac{ac+d}{a-b}$ and $\displaystyle B=-\frac{bc+d}{a-b}$